2018
DOI: 10.1002/art.40392
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Health Care Utilization, End‐Stage Renal Disease, and Mortality Among Medicaid Beneficiaries With Incident Lupus Nephritis

Abstract: In this cohort of patients with incident LN, ESRD and mortality were extremely high overall but were not increased among males compared to females. In this vulnerable population, biologic and health care utilization differences by sex may not significantly affect outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 36 publications
3
22
2
Order By: Relevance
“…Overall, our results suggest a more severe phenotype in male SLE. In contrast to a recent publication [47], the majority of the patients in our study were of European descent, which entails that our findings could represent renal features specific for this population, but not necessarily other populations. In the study by Feldman et al [47], data were collected from the Medicaid Program, which introduces a selection bias.…”
Section: Discussioncontrasting
confidence: 88%
“…Overall, our results suggest a more severe phenotype in male SLE. In contrast to a recent publication [47], the majority of the patients in our study were of European descent, which entails that our findings could represent renal features specific for this population, but not necessarily other populations. In the study by Feldman et al [47], data were collected from the Medicaid Program, which introduces a selection bias.…”
Section: Discussioncontrasting
confidence: 88%
“…An observational study found that compared with women with SLE, men with SLE had fewer outpatient visits and fewer emergency department visits. 16 The authors did not find an association between disparities in health care utilization and disease outcomes, but the effects of such disparities on disease outcomes remain underexplored.…”
Section: Differences In Male and Female Diseasementioning
confidence: 97%
“…Although men with SLE experience nephritis at a higher rate than women, progression to end-stage renal disease does not differ based on sex. 9,[11][12][13][14][15][16] Musculoskeletal involvement appears to be less common in men than in women. 7 The presence of lupus anticoagulant is more frequent in men, but other autoantibodies appear to occur at the same rate.…”
Section: Differences In Male and Female Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Stratification by clinical and serological phenotypes , demography and habits is qualitative, on disease activity measures quantitative 50–57. Stratification on sex, race, socioeconomic status,58–62 access to medical care, medication choice and adherence,63 willingness to participate in clinical trials, doctor–patient interactions,64 patient preferences and perceptions,65 lifestyle choices,66 67 physician choices,68–71 environmental triggers,72–76 poverty,77 social disparities,78 and life events,79 smoking80 and the gut pathobiont81 all affect manifestations and outcomes in ways that dictate who participates in a study on SLE and in ways that cannot be examined in animal models 82. Stratification on gene expression , quantitative, predicts risk and possibly phenotype83–93; SLE-like illnesses (the autoinflammatory diseases),94 Aicardi-Goutières syndrome,95 96 Canale-Smith syndrome97 and SLE associated with immunodeficiency98 suggest mechanisms for primary illness, and for phenotype diversity.…”
Section: Stratificationmentioning
confidence: 99%